2020
DOI: 10.1111/rode.12651
|View full text |Cite
|
Sign up to set email alerts
|

Shared renewable resources and gains from trade under technology standards

Abstract: Using a two-country, two-good model of international trade, we examine gains from trade and strategic interaction in resource management among countries that share renewable resources such as fishery stocks. Two goods are a resource good, which is the harvest of the shared stock, and some other good that may be thought of as manufactures. The productivity of the resource good depends on harvesting technology and the stock level. This paper focuses on technology standards (e.g., restrictions on fishing gears, v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…which is a nonlinear diferential equation. Rearranging equation (11) to transform into a linear equation, frstly rewrite equation ( 11) as follows:…”
Section: The Open-access Renewable Resource Model With Excessive Harv...mentioning
confidence: 99%
See 1 more Smart Citation
“…which is a nonlinear diferential equation. Rearranging equation (11) to transform into a linear equation, frstly rewrite equation ( 11) as follows:…”
Section: The Open-access Renewable Resource Model With Excessive Harv...mentioning
confidence: 99%
“…Upmann and Gromov [10] aimed to demonstrate the structure of optimal eforts for harvesting in the open-access problem under diferent scenarios. Takarada et al [11] examined the open-access resources with shared renewable resource assumption under no resource management. Tis paper characterized that natural resources were not only accessible by local residents, implying that resources were internationally common.…”
Section: Introductionmentioning
confidence: 99%
“…Zimon et al (2020) suggested that the implementation of the ISO 22000 standard was conducive to the development of key stages in the supply chain. Studies of environmental standards (Wilson et al, 2002), quality standards (Maskus et al, 2005;Sánchez et al, 2010), and later studies of low-carbon fuel standards (Lade & Lin Lawell, 2015), air pollution standards (Sankar et al, 2020), dairy and fruit standards (Groot-Kormelinck et al, 2021), and production and product standards (Fernandes et al, 2019;Takarada et al, 2020;Yu & Bouamra-Mechemache, 2016) expressed similar thoughts and investigated whether positive or negative effects predominate.…”
Section: Standards and Tradementioning
confidence: 99%
“…Our basic structure (utility functions, stock evolution equation, production function of both goods, etc.) shares various premises in the analysis of trade and renewable resources such as Brander and Taylor (1997a, 1997b, 1998), Emami and Johnston (2000), Jinji (2007), Rus (2012), Takarada et al (2013), Rus (2016) and Takarada et al (2020). Three papers by Brander and Taylor (1997a, 1997b, 1998) deserved to be examined more closely to understand the main results the literature built on.…”
Section: Introductionmentioning
confidence: 99%